Reading for riches : a Vygotskyan analysis of English writing by D.E.T. matriculants - Faragher, Lynette Dorothy Pears (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEd) -- University of Stellenbosch, 1995.